Perbandingan Implementasi Pengelolaan dan Pemanfaatan Platform Digital dalam Model Penghimpunan Platform Digital dalam Model Penghimpunan Zakat, Infak, dan Sedekah (Respons Lembaga Sosial terhadap Peristiwa ACT) - Noe'man, Muhammad Khirzan Nazar; Aditya, Mochammad Yana; Anwar, Saiful; Aini, Nur; Amelia, Amie (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2026)
This study aims to explore the utilization of digital platforms in the collection of zakat, infaq, and sadaqah (ZIS) by Yayasan Aksi Indonesia Dermawan and Lazismu Jawa Barat (Lazismu Jabar), as well as to analyse each institution’s strategies in addressing public trust challenges following cases of fund misuse by similar organizations. Employing a qualitative approach with a case study method, the research involved six key informants from both institutions. The findings reveal that Aksi Indonesia Dermawan adopts an external digital platform-based approach—such as Kitabisa.com, SharingHappiness.org, and RuangKitaPeduli.org—to expand donor reach and improve fundraising efficiency, despite facing a service fee deduction of 5–7%. In contrast, Lazismu Jabar prioritizes the integration of internal systems and the Muhammadiyah community network to maintain transparency and trust. The key distinction between the two institutions lies in their strategic orientation: Aksi Indonesia Dermawan focuses on the effectiveness of digital marketing and technological adaptation, while Lazismu Jabar emphasizes socio-religious movement values and long-term sustainability. The study also examines how sharia financial principles—particularly regarding the allocation of operational funds (amil) and the interpretation of service fees (ujroh) for digital platforms—are applied within the context of the challenges of digital philanthropy.